Simulation of Web-Based Fiber Optic Network Monitoring Development for Optimizing Infrastructure Maintenance - Cecep Kurnia Sastradipraja; Rr.Isni Anisah Puspowati; Hanhan H Solihin; Agus Alim; Lahmudin Sipahutar; Sain Segar K. Sid (Politeknik Piksi Ganesha Indonesia, 2026)
The rapid expansion of fiber optic networks has increased the complexity of infrastructure management, particularly in joint closure documentation, core configuration, and connection quality monitoring. Manual management and fragmented documentation often lead to inconsistent data, limited traceability, and inefficient maintenance processes. This study aims to develop a web-based fiber optic network management system that integrates asset documentation, core structure visualization, attenuation history recording, location documentation, and reporting into a unified platform. The system was developed using the Software Development Life Cycle (SDLC) with the Waterfall model, including requirement analysis, system design, implementation, and testing. The developed system successfully manages joint closure data, visualizes a 192-core structure, records attenuation measurement history, tracks user activities, and generates digital reports. Functional testing confirmed that all major features performed according to the specified requirements. The integrated system enhances documentation accuracy, accelerates network condition identification, improves maintenance efficiency, and provides an effective solution for comprehensive fiber optic infrastructure management.